THE REALIZATION OF ATTITUDE IN ONLINE NEWS ARTICLE: AN APPRAISAL ANALYSIS - Muhammad Asril Marpaung (Yayasan Pendidikan Islam dan Multikultural, 2022)
The development of mass media from time to time cannot be stopped. In the past, mass media was still in print or commonly referred to as print media. Print media emerged as a means to provide information or news to the public or readers about what is happening in the midst of society. In the past few decades, this media has played a very important role in exploring events or things and issues inherent in society, ranging from political, educational and economic problems. Even today, print media is still a tool of social control for the community and will continue to survive in accordance with the function of the print media itself. Furthermore, how do we news readers respond to every thing that is news online that is still not known to be true. Therefore, the author will examine the attitude towards online reporting.